Notes on twenty-nine species of jumping spiders from South China (Araneae: Salticidae) - Wang, Cheng; Mi, Xiao-Qi; Wang, Wei-Hang; Gan, Jia-Hui; Irfan, Muhammad; Zhong, Yang; Peng, Xian-Jin (European Journal of Taxonomy, 2023)
A taxonomic study on twenty-nine species of jumping spiders from South China is presented. Twenty new species are diagnosed and described: Heliophanoides proszynskii Wang, Mi & Peng sp. nov. (♂♀), Myrmage lii Wang, Mi & Peng sp. nov. (♂♀), Myrmarachne hamata Wang, Mi & Peng sp. nov. (♂), M. xingrenensis Wang, Mi & Peng sp. nov. (♂♀), M. yinae Wang, Mi & Peng sp. nov. (♂♀), Phintella fodingensis Wang, Mi & Peng sp. nov. (♂♀), P. jiugongensis Wang, Mi & Peng sp. nov. (♂♀), P. liae Wang, Mi & Peng sp. nov. (♂), P. liui Wang, Mi & Peng sp. nov. (♂♀), P. subpanda Wang, Mi & Peng sp. nov. (♂♀), P. wandae Wang, Mi & Peng sp. nov. (♂♀), Ptocasius dian Wang, Mi & Peng sp. nov. (♂♀), P. subhubeiensis Wang, Mi & Peng sp. nov. (♂♀), Rhene elongata Wang, Mi & Peng sp. nov. (♂♀), Stertinius donglinsiensis Wang, Mi & Peng sp. nov. (♂♀), S. logunovi Wang, Mi & Peng sp. nov. (♂), Synagelides fanjingensis Wang, Mi & Peng sp. nov. (♂♀), Thyene xingrenensis Wang, Mi & Peng sp. nov. (♂♀), Toxeus fodingensis Wang, Mi & Peng sp. nov. (♂♀), and Yaginumaella zabkai Wang, Mi & Peng sp. nov. (♂♀). The genus Heliophanoides Prószyński, 1992 is redefined and two new combinations, transferred from the genus Phintella Strand, 1906, are proposed: H. tengchongensis (Lei & Peng 2013) comb. nov., and H. longlingensis (Lei & Peng 2013) comb. nov. The unknown sexes of the following six species are described for the first time: Phintella fanjingshan Li, Wang, Zhang & Chen, 2019, P. panda Huang, Wang & Peng, 2015, P. pygmaea (Wesołowska, 1981), P. sancha Cao & Li, 2016, P. wulingensis Huang, Wang & Peng, 2015, and Rhene yunnanensis (Peng & Xie, 1995). Brettus anchorum Wanless, 1979 and Phintella aequipeiformis Żabka, 1985 are newly recorded from China. Icius indicus (Simon, 1901) comb. nov. (transferred from Phintella) is re-described. Phintella levii Huang, Wang & Peng, 2015 is assigned to be a synonym of P. arcuata Huang, Wang & Peng, 2015. Thyene zhangi (Peng, Yin, Yan & Kim, 1998) comb. nov. is transferred from Plexippoides Prószyński, 1984, and T. bilaguncula (Xie & Peng, 1995) comb. nov. is transferred from Ptocasius Simon, 1885. Diagnostic illustrations of the twenty-nine species and the distributional maps of the studied specimens are provided.